Equivalente de redes elétricas aplicado na supervisão de redes de distribuição com inserção de microgeração fotovoltaica distribuída - Gustavo Diniz da Corte (2019)
This thesis approaches the Low Voltage Electrical Networks Supervision topic. More specifically, this work proposes a new methodology which allows monitoring of electrical variables in points of interest. Such methodology is based on the construction of equivalent low voltage networks designed to represent circuits with special features. Among those characteristics, the presence of Distributed Photovoltaic Microgeneration, unbalance of low voltage distribution systems and lack of measurements located near consumers are highlighted. Real time operation of electrical systems is not trivial, particularly in distribution ones, where measurements are commonly centered at substations. This implies in difficulty for obtaining the network state. The presence of photovoltaic generation introduces a new dynamic for systems load behavior, therefore demanding new ways to represent it. Alternative network solution techniques are needed for phase unbalanced circuits. Also, it is important to emphasize that Brazilian distribution systems are extensive. The methodology proposed in this work takes into account the remarks mentioned above. The equivalent developed allows the full network representation using an Equivalent Load/Generation Unit, which enables the joint modelling of loads and photovoltaic generation, and Equivalent Networks, representing the system topology. The equivalent formulation is innovative and is based on the use of adapted Load Flow solution algorithms. The proposed method is tested under different operative network conditions, validating its comprehensive usage. The positive results show the application potential of this methodology for real time low voltage networks supervision.